Counterfeit drugs in India: significance and impact on pharmacovigilance - Shah, Nehal A.; Sattigeri, Bhagya M.; Patel, Nirav N.; Desai, Haresh A. (International Journal of Research in Medical Sciences, 2017)
Counterfeit drugs have emerged as a major global problem. This issue has been brought to the centre of the Indian media due to the death of 15 women attending a sterilization camp in Chhattisgarh. India’s pharmaceutical industry exports drugs worth 15 billion dollars, which means a high prevalence of counterfeiting in India’s drug industry has global repercussions. However, accurate figures on the extent of counterfeit drugs in India are not available. The scientific literature as well as media reports often quotes figures of 10-35%, though studies done by the Indian Government dispute this. Counterfeit drug numbers have been known to be under represented by Governments due to fear of undermining their economy and health systems. On the other hand, rival companies in other countries may have an incentive to over hype India’s counterfeit problem to dent India’s growing status as the leading global supplier of generic medicines. Lack of clear definitions and differences between laws of countries further complicate reporting. A high prevalence of counterfeit drugs has a large impact on both health and economic indicators. Additionally, counterfeit drugs provide significant challenges to Pharmacovigilance programmes. Hence, here we discuss the significance of use of counterfeit drugs in India and challenges faced by Pharmacovigilance due to the extensive use of counterfeit drugs.